2021
DOI: 10.1007/s00408-020-00411-9
|View full text |Cite|
|
Sign up to set email alerts
|

Uniportal Versus Multiportal Video-Assisted Thoracoscopic Lobectomy for Lung Cancer: An Updated Meta-analysis

Abstract: Objective We reviewed the available literature on patients with lung cancer undergoing either uniportal (UVATS) or multiport video-assisted thoracoscopic surgery (MVATS). Methods Original research studies that evaluated perioperative and long-term outcomes of UVATS versus MVATS were identified, from January 1990 to April 2020. The perioperative, along with the oncologic and long-term survival outcomes, were calculated according to either a fixed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…1,2 Furthermore, surgical techniques with fewer incisions, especially the uniportal technique, are associated with less chest pain. [6][7][8] We therefore performed a single utility port robot-assisted right S6 sleeve segmentectomy with three robotic arms, which can further reduce the excess surgical trauma caused by another port or more ports, and simultaneously preserve more functional lung tissues. To the best of our knowledge, this is the first report on robot-assisted sleeve segmentectomy with the single utility port approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Furthermore, surgical techniques with fewer incisions, especially the uniportal technique, are associated with less chest pain. [6][7][8] We therefore performed a single utility port robot-assisted right S6 sleeve segmentectomy with three robotic arms, which can further reduce the excess surgical trauma caused by another port or more ports, and simultaneously preserve more functional lung tissues. To the best of our knowledge, this is the first report on robot-assisted sleeve segmentectomy with the single utility port approach.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Surgical techniques with fewer incisions, especially the uniportal technique, are associated with less chest pain. [6][7][8] Here, we describe an aged patient with decreased pulmonary function whose carcinoid tumor invaded the bronchus originating of the right superior segment (S6), who underwent robot-assisted right S6 sleeve segmentectomy via the single utility port approach with three robotic arms.…”
Section: Introductionmentioning
confidence: 99%
“…Our team started to use "uniportal thoracoscopic major pulmonary resection" in February 2019. The uniportal thoracoscopic approach is considered minimally invasive and has several advantages, including low postoperative pain, few morbidities, short-duration postoperative chest drainage, short hospitalization periods, rapid postoperative recovery, and relatively low medical costs [4][5][6][7] . Magouliotis et al [8] demonstrated more favorable short-term oncological results of a uniportal compared to multiportal approach for thoracic malignancies in their review article, although the long-term outcomes were unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The conventional multiportal VATL with several incisions was alternated to triportal, and recently biportal, or even uniportal VATL. [ 9 , 10 ]…”
Section: Introductionmentioning
confidence: 99%